Optimalisasi Keuntungan Pada Agroindustri Rumah Tangga - Richard P. H. Hawu Lado; Wiendiyati Wiendiyati; Marthen R. Pellokila (Undana Press, 2019)
Sima Indah Home Industry is an industrial in the city of Kupang , which is engaged in the processing of agricultural products to be a special snack product of East Nusa Tenggara . In producing the seven variants of such products Sima Indah Home Industri is expected to use the limited resources (constraints) of labor , raw materials and capital . Thus , the problem can be solved using Linear Programing . This research was conducted to determine the combination of products that can maximize profits and to know the effect of changes in resource components to optimize product combinations on Sima Indah Home Industry. The research was conducted in May 2019 by interviewing the Directur , data collection, constracting matrices, then it was analyzed using Lindo61 software . Based on the analysis using the Lindo61 software, obtained the following results : (1)The profit in one production is Rp.6,190,347 and the analysis result of optimum profit on Sima Indah Home Industry is by producing a combination of products corn shrimp , corn marning , banana chips , and egg beans . The combination of these products can be a benefit of reaching Rp.11,899,630. (2)Analysis of Sensistivities carried out due to changes in the cost of obtaining resources such as changes in the price of raw materials , labor wages and capital limitation that can affect the optimal combination . Due to change the total cost of profit changed into Rp .5,110,347 ; After sensitivity analysis was done the optimization profit obtained Rp.10,811,190 and the optimal combination was change into the product was corn cips, sweet potato chips , banana chips and egg beans . It can be concluded that the changes to the resource component change the optimal combination and change the destination function . Industri Rumah Tangga Sima Indah adalah industri di Kota Kupang, yang bergerak dibidang pengolahan produk pertanian menjadi produk camilan khas Nusa Tenggara Timur. Dalam memproduksi produk tersebut Industri Rumah Tangga Sima Indah diharapkan menggunakan keterbatasan sumberdaya (kendala) tenaga kerja, bahan baku dan modal. Maka permasalahan itu dapat diselesaikan dengan menggunakan Linear Programing.Penelitian ini dilakukan untukmenentukan kombinasi produk yang dapat memaksimalkan keuntungan dan mengetahui pengaruh perubahan komponen sumberdaya terhadap kombinasi produk optimal pada Industri Rumah Tangga Sima Indah. Penelitian ini dilakukan pada bulan Mei 2019 dengan wawancara Dikrektur industri, pengumpulan data, menyusun matriks, kemudian dianalisis dengan aplikasi Lindo61. Berdasarkan analisis dengan menggunakan aplikasi Lindo61,diperoleh hasil sebagai berikut: (1) Keuntungan dalam satu kali produksi adalah sebesar Rp.6.190.347, dan Hasil analisis keuntungan optimum pada Industri Rumah Tangga Sima Indah adalah dengan memproduksi kombinasi produk jagung udang, marning jagung, keripik pisang, dan kacang telur. Kombinasi produk tersebut dapat mamaksimumkan keuntungan mencapai Rp.11.899.630. (2) Analisis sensistivitas dilakukan karena terjadinya perubahan biaya untuk memperoleh sumberdayaseperti perubahan harga bahan baku, besaran upah tenaga kerja dan batasan modal yang dapat mempengaruhi kombinasi optimal. Akibat perubahan biaya total keuntungan berubah menjadi sebesar Rp.5.110.347; Setelah melakukan anilisis sesitivitas, keuntungan optimumnya dapat mencapai Rp.10.811.190 dan merubah kombinasi optimal menjadi kombinasi produk emping jagung, keripik ubi, keripik pisang dan kacang telur. Sehingga dapat disimpulkan bahwa perubahan komponen sumberdaya merubah kombinasi optimal dan merubah besaran fungsi tujuan.